The brief summary of the practical guideline for the treatment of stage I-III periodontitis - according to the EFP clinical practice guideline (2020) - Claudia Paár; Boldizsár Bartha; Mária Eper; Zsombor Radóczy-Drajkó; Gábor Szabó; István Gera (Hungarian Dental Association, 2021)
The recently introduced 2017 World Workshop on the Classification of Periodontitis, changed several definitions and diagnostic approaches. Those were summarized and published in the Hungarian scientific media last year. One of the key elements of the new classification is to make a paradigm change and new perspectives in the understanding of the whole plaque related periodontal diseases. For plaque related periodontitis, the new classification incorporated stages and grades of disease, aiming to describe not only disease severity and extent but also its complexity and the contributing risk factors. Therefor it was wise to formulate evidence-based clinical guidelines for practitioners how manage advanced (stage II-III) periodontitis. The EFP Work Groups based on their panel discussions has recently published a very detailed guideline in the J. Clinical Periodontology (2020; 47: 4-60). Those recommendations cover the whole course of comprehensive periodontal treatment. The aim: of the Hungarian summary of the EFP protocol is to briefly summarize the 55 pages EFP S3 Level Clinical Practice Guideline (S3 CPG) for the Hungarian dentists and scholars. Results: The S3 CPG for the management of stages I, II and III periodontitis used a pre-established stepwise approach to therapy based disease stages. Consensus was achieved on recommendations covering incremental, interventions in all steps of therapy. Treatment planning is focusing on - a) behavioural changes, and supragingival biofilm, gingival inflammation and risk factor control; - b) supra- and sub-gingival instrumentation, with and without adjunctive therapies) different types of periodontal surgical interventions; and - d) the necessary supportive periodontal care to extend benefits over time. Those major elements of periodontal care is briefly summarized in this Hungarian version. Conclusion: This S3 guideline summarizes according to the available evidence at the time of publication the available and most effective methods to treat periodontitis and to maintain periodontal health.